NCAR/NSF C-130 Multichannel Cloud Radiometer. Version 1.0 ... - NCAR/EOL Research Aviation Facility (UCAR/NCAR - Earth Observing Laboratory, 2011)
The MCR is a seven-channel radiometer that scans between ±45° about the NSF/NCAR C-130 track. This dataset contains MCR data collected during the Surface Head Budget of the Arctic Ocean Project (SHEBA). This data can be viewed using MCRVIEW available for download below. ...